Desmoplastic Small Round Cell Tumor: Current Management and Recent Findings. (29th March 2012) - Dufresne, Armelle; Cassier, Philippe; Couraud, Laure; Marec-Bérard, Perrine; Meeus, Pierre; Alberti, Laurent; Blay, Jean-Yves
Abstract : Desmoplastic small round cell tumor (DSRCT) is a rare and highly aggressive mesenchymal tumor that develops in the abdominal cavity of young men adults. Patients typically present with symptoms of abdominal sarcomatosis. Diagnosis is based on histological analysis of biopsies which typically show small round blue cells in nests separated by an abundant desmoplastic stroma. DSRCT is associated with a unique chromosomal translocation t(11:22) (p 13; q 12) that involves the EWSR1 and WT1 genes. The prognosis is particularly poor; median survival ranges from 17 to 25 months, largely due to the presentation of the majority of patients with metastatic disease. Management of DSRCT remains challenging and current schemes lack a significant cure rate despite the use of aggressive treatments such as polychemotherapy, debulking surgery and whole abdominal radiation. Several methods are being evaluated to improve survival: addition of chemotherapy and targeted therapies to standard neoadjuvant protocol, completion of surgical resection with HIPEC, postoperative IMRT, treatment of hepatic metastases with [ 90 Y]Yttrium microsphere liver embolization.